A Novel Alginate-Based Delivery System for the Prevention and Treatment of Pressure-Overload Induced Heart Failure - Kumar, Ambrish; Belhaj, Marwa; DiPette, Donald J.; Potts, Jay D. (Frontiers in Pharmacology, 2021)
Background: α-CGRP (alpha-calcitonin gene related peptide) is a cardioprotective neuropeptide. Previously we demonstrated that administration of native α-CGRP, using osmotic mini-pumps, protected against transverse aortic constriction (TAC) pressure-induced heart failure in mice. However, the short half-life of the peptide and non-applicability of osmotic pumps in human limits the use of α-CGRP as a therapeutic agent for heart failure (HF). Here, we sought to comprehensively study a novel α-CGRP delivery system using alginate microcapsules to assess its bioavailability in vivo and cardioprotective effects in HF mice. Methods: α-CGRP alginate microcapsules (200 µm diameter) were prepared using an electrospray method. Alginate-α-CGRP microcapsules were incubated with two cardiac cell lines, rat H9c2 cells and mouse HL-1 cells, to determine cell cytotoxicity using trypan blue viability assays and calcium dye fluorescent assays. The effectiveness of alginate-α-CGRP microcapsules was tested using a TAC-pressure overload mouse model of heart failure. Male C57BL6 mice were divided into four groups: sham, sham-alginate-α-CGRP, TAC-only, TAC-alginate-α-CGRP. After two or fifteen-days post-TAC, alginate-α-CGRP microcapsules were administered subcutaneously on alternate days, for 28 days, and echocardiography performed weekly. Following 28 days, mice were sacrificed and hearts were collected for further histological and biochemical analyses. Results: Our in vitro cell culture assays demonstrated that alginate-α-CGRP microcapsules didn’t affect the viability of either cardiac cell line. Alginate-α-CGRP microcapsules exhibited an extended release of peptide. Echocardiography, biochemical, and histological results demonstrated that administration of alginate-α-CGRP microcapsules significantly improved all cardiac parameters examined in TAC-mice. Compared to sham mice, TAC significantly decreased cardiac functions (as determined by fraction shortening and ejection fraction) and markedly increased heart and lung weight, left ventricle (LV) cardiac cell size, cardiac apoptosis and oxidative stress. In contrast, administration of alginate-α-CGRP microcapsules significantly attenuated all of the deleterious symptoms induced in TAC mice. Conclusions: Our results demonstrate that alginate encapsulated α-CGRP is an effective strategy to improve peptide bioavailability and increase the duration of the therapeutic effect of the peptide throughout the treatment period. Moreover, alginate mediated α-CGRP delivery, either prior to onset or after initiation of symptom progression of pressure-overload HF, improves cardiac function and protects against pressure-induced heart failure.